Persistence of antipredator behavior in an island population of California quail. (20th December 2017) - Rasheed, Ayesha A.; Hambley, Kristina; Chan, Gabriel; de la Rosa, Carlos A.; Larison, Brenda; Blumstein, Daniel T.
Abstract: Island populations may provide unique insights into the evolution and persistence of antipredator behavior. If antipredator behavior is costly and islands have reduced predation risk, then we expect the reduction or loss of antipredator behavior on islands. However, if even a single predator remains, the multipredator hypothesis predicts that antipredator behaviors will be conserved. We compared the flight initiation distances (FID) of California quail ( Callipepla californica ) on Santa Catalina Island (a location with reduced predation pressure) with quail on the mainland. We found no differences in FID between mainland and island quail. However, despite employing consistent testing methods, the starting distance from which quail were approached was significantly reduced for quail studied on the island when compared with quail studied on the mainland. Our results are consistent with the multipredator hypothesis because, while the island population had substantially fewer predators, some predators remained and some antipredator behavior persisted.